Analisis Kebijakan Asasemen Nasional Pengganti Ujian Nasional terhadap Evaluasi Pendidikan di Indonesia - Fadhilah, Viki; Setiawan, Farid; Indriani, Tiara; Yulianti, Sri (Lembaga Yasin AlSys, 2022)
Minister of Education Nadiem Makarim in 2021 has formulated the National Assessment Policy, this policy is a policy issued by the government in Indonesia a s a substitute for the national exam, which prioritizes reasoning abilities and the application of calculation methods, assessment and morality or character education. So that in the following year the national exams which are usually held in elementary schools, junior high schools and high / vocational schools no longer carry out national exams. The research method in this study is qualitative in nature, by collecting data as a reference source and further research data to describe the problems that occur in accordance with this research, namely the abolition of the national exam which is replaced by a national assessment system. The results of this study are that the policy of the elimination of the national exam greatly influences the final evaluation process of student education, where this abolition is intended to improve the quality of education, because the national exam is deemed less effective due to the lack of government coordination to optimize control of the distribution of questions from the center. The pros and cons of eliminating this national exam must be balanced with mutual support from various parties, so that it is hoped that this national assessment system will run well.